Payers' Perspectives on Pharmacist-Directed Care in a Community Pharmacy Setting. Issue 9 (September 2019) - Merrill, Bradley S.; Tak, Casey R.; Feehan, Michael; Munger, Mark A.
Background: The United States is spending an increasing share of its national income on health care while American citizens are not receiving the commensurate benefit of longer, healthier lives. Pharmacists are in a position to provide high-quality care; however, a paucity of data exists on payers' perspectives on insurance reimbursement for pharmacist-provided, community-delivered clinical services.Objective: To understand payers' perspectives toward pharmacist-provided community-delivered advanced clinical services.Methods: A 15-minute online survey was administered to determine payers' preferences and attitudes of impact about care being provided in a community pharmacy setting by a pharmacist.Results: The study recruited 50 payers from a diverse set of US organizations. The likelihood for reimbursement for a suite of pharmacist-provided, community-delivered clinical services was likely/very likely (66%), neutral (22%), and unlikely/very unlikely (12%). Pharmacists were viewed positively by payers for the provision of these services. Payers think that more clinical services should be offered in the community pharmacy. Trust in pharmacist-provided information services on general health and medications, and pharmacist competency were strongly positive.Conclusions and Relevance: A quantitative assessment of payer attitudes for pharmacist-provided, community-delivered advanced clinical practice was positive. Payers were positive about pharmacist contributions to the provision of heath and medication information. Continued development and deployment of advanced clinical services at the community pharmacy appears to be a financially viable model.